The methods of improving intonation among violinists and violists in Faculty of Music, UiTM Shah Alam / Fazrina Shariff Udin - Shariff Udin, Fazrina (Faculty of Music, 2017)
The purpose of this study was to know the methods of improving intonation among violinists and violists in Faculty of Music, UiTM. The study was conducted at the Faculty of Music, UiTM Shah Alam among degree students in the faculty. The samples of this study were the violinists and violist from Faculty of Music, UiTM. The respondents for this study were 3 violinists and 1 violist. There are three respondents from bachelor of music education and one of the respondent from bachelor of music performance. The findings of this study discuss the methods of improving intonation when practicing. The data of the study was collected through face interview sessions with the use of qualitative method.